Ketimpangan Pendidikan dan Peluang Kerja: Perspektif Teori Interaksionisme Simbolik - Octavina, Mely Tri (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2024)
This study aims to determine the effect of educational inequality and employment opportunities on the perceptions and social interactions of individuals in looking for work in Surabaya using the perspective of symbolic interactionism theory. The research method used is a qualitative approach with data collection techniques through in-depth interviews and participant observation of 15 job seekers in Surabaya. The results of the study show that inequality of education and job opportunities in Surabaya is still a significant problem, which has led to interest between the quality of education and skills possessed by job seekers and the needs of the job market. It also has an impact on anger and anger. Social perceptions and interactions play an important role in job search, where symbols such as diplomas, certificates, work experience, and social connections influence individual perceptions and social interactions in job search. The theory of symbolic interactionism makes a significant contribution to understanding perceptions and social interactions in the context of educational inequality and employment opportunities in Surabaya. This theory suggests that social human action is based on the interpretation of symbols used in social interaction. The results of this research have important implications for development policy, especially in addressing inequality in education and job opportunities in Surabaya and increasing job opportunities for job seekers. In addition, the theoretical implicit of this research can be used as a basis for developing a theory of symbolic interactionism in the context of education and employment opportunities